Investigation of the effect of short-pulsed ion irradiation on the stability of carbon nanowalls - Yerlanuly, Y. (Recent Contributions to Physics, 2026)
Carbon nanowalls (CNWs) are promising carbon-based nanomaterials for radiation-resistant electronic and optoelectronic applications due to their unique three-dimensional graphene-like architecture and outstanding physicochemical properties. In this work, the effect of short-pulsed high-current ion irradiation on the stability of carbon nanowalls was systematically investigated. CNWs were synthesized on quartz substrates by inductively coupled plasma–enhanced chemical vapor deposition and subsequently irradiated using the high-current pulsed ion accelerator INURA at current densities of 4, 7, and 10 A/cm2. The radiation-induced changes in morphology, structure, optical transparency, and electrical properties were analyzed using atomic force microscopy, Raman spectroscopy, UV–Vis spectrophotometry, and four-point probe measurements. Atomic force microscopy revealed only moderate surface rearrangement and slight variations in roughness, while the characteristic vertically oriented nanowall morphology was preserved even at the highest irradiation density. Raman analysis confirmed the retention of the graphene-like sp2 carbon structure, with minimal changes in the ID/IG ratio, indicating limited defect formation. Optical measurements showed moderate variations in transmittance correlated with surface restructuring, without spectral degradation. Electrical characterization demonstrated a stable or slightly reduced sheet resistance after irradiation, suggesting improved interwall electrical contact and structural stabilization. Overall, the results demonstrate the high resistance of carbon nanowalls to short-pulsed ion irradiation and confirm their suitability as functional materials for radiation-resistant electronic, optoelectronic, and sensor devices.
Keywords: carbon nanowalls; ion irradiation; radiation resistance; short-pulsed ion beam; surface morphology; Raman spectroscopy; electrical properties